2020
DOI: 10.3390/diagnostics10121066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parameters for Estimating the Postmortem Interval of Skeletal Remains Using Bovine Femurs: A Pilot Study

Abstract: The postmortem interval (PMI) of victims is a key parameter in criminal investigations. However, effective methods for estimating the PMI of skeletal remains have not been established because it is determined by various factors, including environmental conditions. To identify effective parameters for estimating the PMI of skeletal remains, we investigated the change in bone focusing on the amount of DNA, element concentrations, and bone density that occurred in the bone samples of bovine femurs, each maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Bone samples were divided into four groups based on PMI, and it was found that the expression of target microRNA in bone samples from group 1 (PMI < 1 month) was statistically different from other groups. Other research focused on microRNA with similar conclusions and shorter PMI [48][49][50].…”
Section: Small Particles For Pmi: Evaluation Of Bone Components Inclu...mentioning
confidence: 55%
“…Bone samples were divided into four groups based on PMI, and it was found that the expression of target microRNA in bone samples from group 1 (PMI < 1 month) was statistically different from other groups. Other research focused on microRNA with similar conclusions and shorter PMI [48][49][50].…”
Section: Small Particles For Pmi: Evaluation Of Bone Components Inclu...mentioning
confidence: 55%
“…Three elemental measurements of the outer edge of the cortical bone were taken per sample and averaged to give one overall reading per sample. Eight elements were selected using current literature 34 , 52 as guidance; calcium and phosphorus to represent bone minerals, potassium, sodium, and iron to represent bodily fluids, and magnesium, zinc, and barium to represent trace elements. For analysis, the mass (%) of each selected element was calculated using analytical software in standardless quantitative mode.…”
Section: Methodsmentioning
confidence: 99%
“…41 A loss in iron has also been observed <12 months PMI and has been associated with the breakdown of blood cells. 34 Studies have also noted changes to zinc, 52 manganese, and magnesium 41 occurring over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation